EGFR-mediated interleukin enhancer-binding factor 3 contributes to formation and survival of cancer stem-like tumorspheres as a therapeutic target against EGFR-positive non-small cell lung cancer. (February 2018) - Cheng, Chun-Chia; Chou, Kuei-Fang; Wu, Cheng-Wen; Su, Nai-Wen; Peng, Cheng-Liang; Su, Ying-Wen; Chang, Jungshan; Ho, Ai-Sheng; Lin, Huan-Chau; Chen, Caleb Gon-Shen; Yang, Bi-Ling; Chang, Yu-Cheng; et al.
Highlights: ILF3 was a downstream protein of EGFR and mutually regulated EGFR expression. ILF3 regulated expressions of oncogenic receptor, including ErbB3, IGF1R, and FGFR4. Targeting to ILF3 inhibited formation of A549-derived cancer stem-like tumorspheres. Targeting to ILF3 by YM155 synergized the therapeutic efficacy of afatinib. ILF3 was a potential therapeutic target against EGFR-positive lung cancers. Abstract: Objectives: YM155, an inhibitor of interleukin enhancer-binding factor 3 (ILF3), significantly suppresses cancer stemness property, implying that ILF3 contributes to cell survival of cancer stem cells. However, the molecular function of ILF3 inhibiting cancer stemness remains unclear. This study aimed to uncover the potential function of ILF3 involving in cell survival of epidermal growth factor receptor (EGFR)-positive lung stem-like cancer, and to investigate the potential role to improve the efficacy of anti-EGFR therapeutics. Materials and methods: The association of EGFR and ILF3 in expression and regulations was first investigated in this study. Lung cancer A549 cells with deprivation of ILF3 were created by the gene-knockdown method and then RNAseq was applied to identify the putative genes regulated by ILF3. Meanwhile, HCC827- and A549-derived cancer stem-like cells were used to investigate the role of ILF3 in the formation of cancer stem-like tumorspheres. Results: We found that EGFR induced ILF3 expression, and YM155 reduced EGFR expression. The knockdown of ILF3 reduced not only EGFR expression in mRNA and protein levels, but also cell proliferation in vitro and in vivo, demonstrating that ILF3 may play an important role in contributing to cancer cell survival. Moreover, the knockdown and inhibition of ILF3 by shRNA and YM155, respectively, reduced the formation and survival of HCC827- and A549-derived tumorspheres through inhibiting ErbB3 (HER3) expression, and synergized the therapeutic efficacy of afatinib, a tyrosine kinase inhibitor, against EGFR-positive A549 lung cells. Conclusion: This study demonstrated that ILF3 plays an oncogenic like role in maintaining the EGFR-mediated cellular pathway, and can be a therapeutic target to improve the therapeutic efficacy of afatinib. Our results suggested that YM155, an ILF3 inhibitor, has the potential for utilization in cancer therapy against EGFR-positive lung cancers.